CORRELATION BETWEEN MOTHER’S KNOWLEDGE AND ATTITUDE TOWARDS EXCLUSIVE BREASTFEEDING IN KEDIRI - Wafirotul Rizqi Hasanah; Dominicus Husada; Esti Yunitasari (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: The coverage rate of exclusive breastfeeding in Indonesia is still relatively low from the achievement of the national target. Kabupaten Kediri  decreased in exclusive breastfeeding coverage from 62.4% to 56.3%. Kecamatan Ringinrejo is one of the sub-districts with the lowest proportion of exclusive breastfeeding, which is 58.6%. The most influential thing in decreasing the exclusive breastfeeding coverage rate in this region is the mother's knowledge and attitude towards exclusive breastfeeding. Methods: This study used a cross-sectional approach. The number of samples studied were 77 people who had babies aged 6-12 months, lived with their children, and with mother’s own care in the Kecamatan Ringinrejo. Samples were taken using purposive sampling. The independent variables are knowledge and attitudes of mothers. The dependent variable is exclusive breastfeeding. Data were collected using interviews according to the questionnaire. Data analysis using fisher exact test. Results: Knowledge does not affect exclusive breastfeeding with p-value = 0.619 and attitudes do not affect exclusive breastfeeding with p-value = 0.531 Conclusion: there is no relationship between knowledge on exclusive breastfeeding and there is no relationship between attitudes towards exclusive breastfeeding in the Ringinrejo, Kediri. Support from health workers and families need to be increased so that mothers are more committed to exclusive breastfeeding.Keywords: Knowledge, attitude, and exclusive breastfeeding